Seroprevalence of Pertussis in Adults at Childbearing Age Pre- and Post- COVID-19 in Beijing, China - Chen Zhiyun; Pang Jie; Zhang Yuxiao; Ding Yiwei; Chen Ning; Zhang Nan; He Qiushui (MDPI, 2022)
The number of reported pertussis cases has significantly decreased during the coronavirus disease 2019 (COVID-19) pandemic under the influence of strict public health measures in many countries including China. This study evaluated the prevalence of serum anti-pertussis toxin (anti-PT) IgG antibodies in adults at childbearing age pre- and post- COVID-19 in Beijing, China. Altogether, 2021 serum samples collected from individuals aged 20 to 39 years who attended an annual health examination at the Sixth Medical Center of PLA General Hospital, Beijing, in 2018--2020 were measured by ELISA. The median concentration of anti-PT IgG antibodies among participants in 2020 (2.96 IU/mL) was significantly lower than that in 2018 (3.27 IU/mL) (p = 0.011) and in 2019 (3.24 IU/mL) (p = 0.014). The percentage of participants with anti-PT IgG antibodies higher than 40 IU/mL (indicating a pertussis infection within the past few years) was 1.79% (9/503) in 2018, 2.04% (15/735) in 2019 and 1.66% (13/783) in 2020, respectively. The corresponding numbers of the non-detectable (<5 IU/mL) rate of anti-PT IgG antibodies were 66.60%, 65.99% and 70.24%. Our results showed that there was a significant difference between true and reported incidence rates even during the COVID-19 pandemic. The proportion of adults at childbearing age without pertussis-specific antibodies is high, suggesting that booster vaccinations in adults should be considered in this country.